A autonomia da escola : a visão dos governos e dos profissionais da educação - Bayerl, Claudia Araujo dos Santos (2006)
The first objective of the dissertation consisted of identifying the concept of autonomy in the public politics that attain direct or indirectly in the administration of the school units, as well as to apprehend the concept of school s autonomy for the professionals that act in your day by day. In this sense, the research was accomplished in two stages. The first felt through the legislation analysis, of official documents and of pertinent bibliography with prominence for the reality of the Municipal district and of the State of Rio de Janeiro. We argued that although most of the studied politics, although in a superficial way, announce to long for the autonomy, little are the ones that expose the conception of autonomy of the school units in a clear way and, mainly, the form for which the schools would reach that autonomy. In the second stage of the study, we accomplished interviews with teachers, school leaders and a technician-administrative employee belonging to different schools of the Municipal district and the State of Rio de Janeiro. In the reports, some teachers affirmed to ignore the educational politics what it can indicate that the democratic administration has not been a reality. We argued, in the final considerations, that the autonomy of the school units is directly related to the degree of deep of the democratic experience in each school and that, therefore, a school indeed autonomous it would be that in that your administration bases on the active participation of your members that, while a organized group, they interact consciously with the subjects local, of the situation and the society structure. In this perspective, your members should be aware of the paper that the school represents and it should represent so much for your destined public, as for the transformation or perpetuity of the social structures and to have conscience of that paper implicates, among other factors, to have science of the politics that regulate the schools operation.